1982
DOI: 10.1002/j.1537-2197.1982.tb13289.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Study of Camellia Japonica Pollen Treated With Myrmicacin, an Ant‐origin Inhibitor

Abstract: The germination and tube growth of Camellia japonica pollen were stopped on a myrmicacincontaining (50–200 ppm) culture medium, but were restored again when the pollen grains were transferred to a myrmicacin‐free medium. Myrmicacin inhibits the movement of Golgi vesicles utilized for the formation of the callose layer in the pollen grain before the germination, and the growing tube tip wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is an inhibitor of the growth and spore germination of a variety of bacteria and fungi (Schildknecht, 1976;Maschwitz, Koob and Schildknecht, 1970). Of even greater interest, a series oflaboratory experiments have shown that myrmicacin, applied in minute quantities to pollen cultures, inhibits pollen germination and retards pollen tube growth Iwadare, 1978, 1979;Iwanami et aI., 1979Iwanami et aI., , 1981Nakamura, Miki-Hirosige and Iwanami, 1982). Since pollen growth is disrupted when subjected to ant secretions in the lab, does it suffer a similar fate when exposed to living, intact ants?…”
mentioning
confidence: 99%
“…It is an inhibitor of the growth and spore germination of a variety of bacteria and fungi (Schildknecht, 1976;Maschwitz, Koob and Schildknecht, 1970). Of even greater interest, a series oflaboratory experiments have shown that myrmicacin, applied in minute quantities to pollen cultures, inhibits pollen germination and retards pollen tube growth Iwadare, 1978, 1979;Iwanami et aI., 1979Iwanami et aI., , 1981Nakamura, Miki-Hirosige and Iwanami, 1982). Since pollen growth is disrupted when subjected to ant secretions in the lab, does it suffer a similar fate when exposed to living, intact ants?…”
mentioning
confidence: 99%